'The Bell Curve' in Perspective Race, Meritocracy, Inequality and Politics - Tucker, William H. (Palgrave Studies in the Theory and History of Psychology, 2024)
This open access book examines the implications of The Bell Curve for the social, economic, and political developments of the early 21st century. Following a review of the reception of The Bell Curve and its place in the campaign to end affirmative action, Professor Tucker analyses Herrnstein's concept of the "meritocracy" in relation to earlier 20th century eugenics and the dramatic increase in economic inequality over the past 30 years. Tucker demonstrates how, contrary to The Bell Curve's predictions, the reallocation of these huge sums was neither rational nor beneficial for society. The book moves on to situate The Bell Curve within contemporary politics and shows how it can be seen to have played a role in the 2016 US election. This compelling analysis will appeal to scholars and those with an interest in the history of scientific racism, the history of psychology and the sociology of knowledge and science. This is an open access book.